EVALUATION OF INDIGENOUS PLANT EXTRACTS AGAINST JASSID, Amrasca bigutulla bigutulla I. (CICADELLIDAE: HOMOPTERA) ON OKRA - AHMAD, SHAHBAZ (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Okra (Abelmoschus esculentus) is an herbaceous annual plant in the family Malvaceae which is grown for its edible seed pods as a vegetable crop. Amrasca bigutulla bigutulla I. causes severe economic losses by sucking the plant sap and restricting photosynthesis through leaf curling. Plant extracts have broad-spectrum insecticidal properties on soft-bodied insects; therefore, they may be used as an alternative to synthetic insecticides. The study was conducted to evaluate the effectiveness of botanicals viz., Nicotiana tabacum, Azadirachta indica, Acacacia nilotica, Citrus aurantiun and Cassia fistula. The observations were taken after 1st, 3rd, 5th and 7th day of application. The percent control, in all the treatments after 24 hours ranged from 0 to 72.50%. Similarly, the percent mortality recorded after 3rd day of application variated from 25 to 75.35%. After the 5th and 7th day of application, a decline was seen in the jassid mortality in all the treatments except Azadirachta indica. In conclusion, the botanicals provided up to 70% jassid control which was significantly higher and could be a recommendation for the Integrated Pest Management program of jassids.